RACIAL SEGREGATION IN LANGSTON HUGHES’S “I, TOO” - Utama, Fajri Khaimara (LANTERN (Journal on English Language, Culture and Literature), 2017)
“I, Too”is a poem written by Langston Hughes. The poem tells us about how the racial segregation happened between the whites and the blacks in America. In this paper, the writer analyzes the racial segregation by discussing intrinsic and extrinsic aspects in this poem. For the intrinsic elements the writer describes imagery and diction and for the extrinsic elements the writer describes racism. From this discussion it can be concluded that the whites think their social status are higher than the blacks are and the whites regard the blacks as slaves not as citizens of America, while the blacks believe that someday the whites will realize that they are wrong and will be ashamed. The blacks hope that they will have the same rights as the whites.